2005
DOI: 10.1115/1.2073628
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical and Experimental Investigation of Transitional Pulsatile Flow in a Stenosed Channel

Abstract: In the present paper, a closely coupled numerical and experimental investigation of pulsatile flow in a prototypical stenotic site is presented. Detailed laser Doppler velocimetry measurements upstream of the stenosis are used to guide the specification of velocity boundary conditions at the inflow plane in a series of direct numerical simulations (DNSs). Comparisons of the velocity statistics between the experiments and DNS in the post-stenotic area demonstrate the great importance of accurate inflow conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…Results, not far from Newtonian cases, focus on transition from stable to unstable flow once Bingham and Reynolds numbers are assigned. Beratlis et al (2005) merges experimental (Doppler) and numerical approaches to correlate blood flow field upstream and downstream of a stenosis. In Lorenzini (2005), instead, a GPL code is used to simulate coronary blood flow as affected by an intravascular Doppler catheter; among the rheologies tested, results show that the two-phase nature of blood requires a nonNewtonian (Cassonian) description to well consider the shear stress effect.…”
Section: Introductionmentioning
confidence: 99%
“…Results, not far from Newtonian cases, focus on transition from stable to unstable flow once Bingham and Reynolds numbers are assigned. Beratlis et al (2005) merges experimental (Doppler) and numerical approaches to correlate blood flow field upstream and downstream of a stenosis. In Lorenzini (2005), instead, a GPL code is used to simulate coronary blood flow as affected by an intravascular Doppler catheter; among the rheologies tested, results show that the two-phase nature of blood requires a nonNewtonian (Cassonian) description to well consider the shear stress effect.…”
Section: Introductionmentioning
confidence: 99%
“…Some assumed the blood flow in coronary arteries to be laminar (7)(8)(9)(10)(11)(12)(13)(14) and behave as Newtonian fluid (8,(15)(16)(17) and some studied turbulence transition and non-Newtonian effects considering idealized straight arterial model with single model stenosis obstruction (11,15,(17)(18)(19)(20)(21). Several experimental investigations have been carried out on flow disturbances in the downstream region of idealized modeled stenosis (18,22,23). Ahmed and Giddens (24) examined the development of flow disturbances downstream of smooth 25%, 50% and 75% area reductions in an idealized geometry and observed a substantial increase in the disturbance level above 50% stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed and Giddens (24) examined the development of flow disturbances downstream of smooth 25%, 50% and 75% area reductions in an idealized geometry and observed a substantial increase in the disturbance level above 50% stenosis. Beratlis et al (18) conducted both numerical and experimental investigation of transitional pulsatile flow in a prototypical stenotic site giving a blockage ratio of 50% and Reynolds number of 570. They used direct numerical simulations (DNS) to study the flow disturbances downstream of the constriction and observed that distal region is dominated by alternating random fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…The consideration of turbulent flow in the pulsatile form has been studied by Varghese and Frankel [24] with both cosine and trapezoidal shaped stenosis. A numerical and experimental investigation of transitional pulsatile flow in a circular shaped stenosed channel has been carried by Beratlis et al [25]. Sherwin and Blackburn [26] have studied the threedimensional instabilities and transition to turbulence of steady flow, steady flow plus an oscillatory component, and an idealized vascular pulsatile flow in a tube with a smooth axisymmetric sinusoidal constriction.…”
Section: Introductionmentioning
confidence: 99%